Improving Strategic Planning and Ensuring the Development of Enterprises Based on Relational Strategies - MAKEDON, Viacheslav; BUDKO, Oksana; SALYGA, Kostiantyn; MYACHIN, Valentin; FISUNENKO, Nadiia (Theoretical and Practical Research in Economic Fields, 2024)
The article is aimed at improving the strategic planning processes at enterprises through the effective implementation and use of relational strategies. These strategies are aimed at increasing the competitiveness, sustainability, and adaptability of enterprises in the face of rapidly changing market realities. The study aims to provide a comprehensive understanding of relational strategies as a strategic planning tool that can contribute to the development of more effective strategic initiatives. The methodological basis of the study includes the use of evolutionary planning, which involves building a long-term model of enterprise development, a methodology for implementing strategic changes that allows assessing the organization’s ability to adapt to innovations, and a systematic planning approach to detail key milestones for achieving strategic goals. The main result of the study was the identification of the peculiarities of forming a relational strategy of an enterprise. Relational strategies are based on the creation of bilateral relations between the enterprise and other market participants, which contributes to the formation of mutually beneficial cooperation. The main goal is to obtain relational rent and ensure sustainable development of the enterprise through collaboration. The key elements of a relational strategy are an understanding of the concept of “relational rent” and the importance of “relational assets”. The study reveals the importance of relational strategies in modern strategic planning of enterprises, highlighting them as an important tool for achieving competitive advantage, sustainability and effective adaptation to dynamic market conditions